Performance Study Of Calcium Hypochlorite On Wastewater Treatment System From Biomass Gasification Water Scrubber - Lee, Shu Xian (Universiti Sains Malaysia, 2017)
Performance of calcium hypochlorite [Ca(OCI)2] was investigated to determine the suitability to treat the wastewater from biomass gasifier water scrubber. This research also reviews the technical applicability of physic-chemical treatment for the removal of heavy metal(zinc) from Biomass Gasification Plant (BGP)-generated tar-containing wastewater. A particular focus is given to coagulant precipitation through Jar Test to determine the optimal operating conditions which include pH, dose required, initial metal concentration and treatment performance. It is evident from the experiment that calcium hypochlorite are the most frequently studied and widely applied for the treatment used for disinfectant, chlorination, oxidant and removal of metal-contaminated wastewater. 1g/L of calcium hypochlorite has achieved a complete removal of zinc with an initial concentration of 31.5 mg/L. The results are comparable to that of different retention times and temperature. Regarding the available chlorine content, the treated solutions tend to be stable to 1 days of storage when kept at 6°C or at 20°C as the heat contribute to the instability of the solutions. Calcium hypochlorite solutions are extremely alkaline and showed an increase in pH when the concentration of calcium hypochlorite increase. It is important to note that overall treatment cost of wastewater varies, depending on the process employed, quality of wastewater and the local conditions. In general, the technical applicability, plant simplicity and cost effectiveness are the key factors in selecting the most suitable treatment for inorganic effluent.